Dietary patterns and hypertension in Chinese adults: a systematic review and meta-analysis - Wu, Xi; Liu, Jianwei; Wang, Zhuofeng; Chen, Shangya; Ma, Jiazi; Cao, Mao; Yang, Yong; Wu, Guangjian; Li, Wentao; Du, Zhongjun (Frontiers in Public Health, 2025)
ObjectiveNumerous studies have explored the correlation between dietary patterns and the risk of hypertension, yet the findings have remained indeterminate. We performed a meta-analysis to evaluate how various dietary patterns relate to hypertension risk in the Chinese population.MethodsRelevant articles published from 1 January 2004 to 14 March 2024 in five databases (PubMed, Scopus, Web of Science, CNKI, and VIP) were searched. Fixed or random-effects models were employed to estimate the multivariable-adjusted odds ratios (ORs) and 95% confidence intervals (CIs) comparing the highest and lowest categories of dietary patterns.ResultsIn total, 22 articles were incorporated into the meta-analysis. The pooled results indicated a reduced likelihood for hypertension in the highest compared to the lowest category of the traditional southern Chinese pattern (OR = 0.95, 95% CI: 0.92–0.97, p < 0.001). In addition, compared to the lowest category of fruit and dairy pattern, the risk of the highest category had a 25% reduction in hypertension risk (OR = 0.75, 95% CI: 0.64–0.89, p = 0.001). Nevertheless, there was no significant correlation between the animal food pattern and the odds of hypertension (OR = 1.06, 95% CI: 0.98–1.15, p = 0.171).ConclusionThe traditional southern Chinese pattern as well as the fruit and dairy pattern was a protective factor for hypertension. High-quality, large-scale studies are needed to confirm the findings of the current meta-analysis further.